Reliability and Validity of the Auditory Brainstem Response - Zenker, Franz; Barajas de Prat, José Juan (Auditio, 2025)
Electrophysiological recordings allow the evaluation of the functional integrity of the peripheral and central auditory structures. Among them, the Auditory Brainstem Responses (ABR) are a fundamental tool for the study of the neurophysiology of the auditory pathways. Due to the low amplitude and the unavoidable noise contamination, both biological and external, the use of procedures that improve the quality and definition of the recordings obtained is required. This study aims to evaluate ABR’s reliability and validity. Reliability is analyzed through the Standard Deviation Ratio (SDR); and the Correlation Coefficient between Replicates (CCR); which allow for assessing the consistency and reproducibility of the responses. Weighted averaging improves the signal-to-noise ratio (SNR) and reduces the time required for electrophysiological evaluation. Convergent validity evaluates the correlation between electrophysiological and behavioral tests when measuring the same construct, in this case, auditory perception. Criterion validity determines the scale in which a test correlates with an external reference variable, such as the degree of hearing loss or the clinical diagnosis of hearing loss. Different statistical procedures arise to establish the auditory thresholds through the ABRs. It’s postulated that, in order to estimate the auditory thresholds through ABRs, each institute must establish its own control group. Additionally, the most commonly used procedures are analyzed to improve the correlation between ABRs and behavioral responses.